2010
DOI: 10.1161/strokeaha.109.558742
|View full text |Cite
|
Sign up to set email alerts
|

Low Levels of Antibodies Against Phosphorylcholine Predict Development of Stroke in a Population-Based Study From Northern Sweden

Abstract: Background and Purpose-Natural immunoglobulin M antibodies specific for phosphorylcholine (anti-PC) have been implicated in atherosclerosis. We have shown previously that high levels of anti-PC predict a slower progression of atherosclerosis in humans and that low levels of anti-PC are associated with higher risk for cardiovascular disease. Here we determine the association between anti-PC and the incidence of stroke. Methods-Using a nested case control study design, we examined 227 incident cases (125 men and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 38 publications
6
27
0
Order By: Relevance
“…Subsequent research has demonstrated that anti-PC aids in clearance of apoptotic cells (6,30) and prevents the formation of pathogenic foam cells in atherosclerosis by clearing oxidized low density lipoprotein (1). Murine studies with PC vaccination have shown strong beneficial effects on experimental atherosclerosis in vivo (11)(12)(13), and human epidemiology has consistently linked anti-PC insufficiency to cardiovascular events (14)(15)(16)(17). These findings in combination with earlier knowledge on the presence of T15 B cells in germ-free mice (20) has led to the formulation of a hypothesis that germlineencoded PC-reactive Abs produced by innate B1 cells fulfill an important housekeeping function in human physiology (8,10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent research has demonstrated that anti-PC aids in clearance of apoptotic cells (6,30) and prevents the formation of pathogenic foam cells in atherosclerosis by clearing oxidized low density lipoprotein (1). Murine studies with PC vaccination have shown strong beneficial effects on experimental atherosclerosis in vivo (11)(12)(13), and human epidemiology has consistently linked anti-PC insufficiency to cardiovascular events (14)(15)(16)(17). These findings in combination with earlier knowledge on the presence of T15 B cells in germ-free mice (20) has led to the formulation of a hypothesis that germlineencoded PC-reactive Abs produced by innate B1 cells fulfill an important housekeeping function in human physiology (8,10).…”
Section: Discussionmentioning
confidence: 99%
“…Although our data does not preclude the possibility of germline encoded innate anti-PC in humans, it seems clear that in adults, if present, this putative innate response is overshadowed by an adaptive thymus independent-process mediated by conventional B cells. Innate or not, this is still a clinically relevant immune response, and multiple studies have consistently confirmed that having a low titer of anti-PC is an independent risk factor for cardiovascular disease (14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a case in point, anti-ChoP antibodies that bind to dental plaque bacteria cross-react with oxidized low-density lipoprotein (oxLDL), which contains ChoP (104). Reduced anti-ChoP IgM levels in patients with acute cardiovascular disease correspond with increased risk of a new cardiovascular event (105,106). Also, higher anti-ChoP IgM levels correlate with decreased symptomology for systemic lupus erythematosus (SLE) patients (107).…”
Section: Host Responses To Chopmentioning
confidence: 99%
“…15 This association appears to be accentuated in stroke. 16 Furthermore, low levels of IgM anti-PC were associated with SLE in a nested case-control SLE study 17 and in a new SLE case-control study (unpublished); further anti-PC was antiinflammatory, inhibiting the effects of inflammatory phospholipids. 17 Thus, low anti-PC could predispose to both atherosclerosis and rheumatic disease, illustrating 1 possible common underlying factor that deserves further study.…”
Section: See Accompanying Article On Page 1014mentioning
confidence: 97%